The design and prototyping of a Transcatheter Aortic Valve Implantation training system specific for aortic valve regurgitation. - Nkoma, Fakih Fadi (Division of General Surgery, 2024)
Aortic regurgitation (AR) caused by rheumatic heart disease is a significant cause of mortality in developing countries. The replacement of the regurgitant aortic valve was historically performed by surgical insertion of a bioprosthetic or mechanical heart valve. Transcatheter Aortic Valve Implantation (TAVI) has become a common surgical procedure to replace defective aortic valves. The balloon-expandable (BE) transapical TAVI technique involves, a replacement valve crimped onto an inflatable medical balloon and delivered in the aortic valve by making a small incision in the chest and going through the apex of the heart. Once the crimped replacement valve is in position the balloon is inflated, expanding the replacement valve in the native aortic valve, and pushing the native leaflet onto the side. The balloon is then deflated and removed from the heart leaving the prosthetic valve in position. Strait Access Technologies (SAT), a South-African start-up has developed an in innovative lowcost BE transapical TAVI for people suffering from AR. The delivery device consists of a nonocclusive balloon, allowing blood to flow freely during the entire procedure, and uses three locating arms called trunks for easy implantation through temporary anchoring tactile feedback. Compared to majority of the delivery system in the market the heart of the patient doesn't need to be stopped when the SAT delivery device is being used and minimal imaging system is required during the implantation procedure. After determining the optimal orthogonal projection of the aortic root using fluoroscopy and following the right cusps rule, each trunk is positioned in an aortic leaflet cusp to keep relative motion between the delivery device and the heart, and to locate the valve axially and rotationally. Once the trunks are in position the surgeons apply a small force and get tactile feedback to confirm positioning. The force applied during the tactile feedback procedure causes the native leaflets to droop. The droop can be defined as the displacement of the leaflet in the axial direction due to the pull force of the trunks. The amount of droop affects the axial positioning of the valve which is critical as is can led to regurgitation or valve embolization which can potentially be fatal. It has been shown that the complication rate during TAVI reduces drastically after the first 100 implantation, hospitals with high volumes of TAVI have better outcomes. Surgeon proficiency in TAVI procedures can be achieved in multiple ways including workshops, course, simulation and animal trial. Training is important when surgeons are introduced to new technologies. The training methods and the repeat practice can drastically improve their clinical outcome. Most training systems currently available do not indicate the droop of the leaflet based on the force applied. This study aims to define the relationship between the force applied during anchoring of the trunks and the native leaflet droop, to determine and quantify the force required to accurately position the valve, and, to develop a training rig to train surgeons in the correct use of the device. v To do so a pull-force tool replicating the trunks of the delivery device was designed and coupled to a force gauge. Three radiopaque markers were inserted into cadaveric pig hearts connected to a pulsatile pump replicating the blood flow. The pull-force tool was inserted in the pumping heart anchored in the native leaflet and pulled to cause droop. The forces applied on the native leaflet and the droops were recorded under fluoroscopy. Three equations defining the relationship between the droop and the force applied per leaflet were then defined. The force required to position the valve accurately was calculated. A training rig was also developed to train surgeons on the use of the delivery device and was divided into three main parts: an imaging system, a circulatory loop, and a force indication device. The imaging system was designed based on the Phillips BV Pulsera C-arm. It was designed to have similar dimensions, and the same degrees of movement as the image needs to be in a specific orientation for follow the right cusps rule, and to hold a standard security camera that projects the images on a screen to replicate the fluoroscopy imaging the surgeon will see during the procedure. The circulatory loop was designed using 3D printed clear materials and replicating the native anatomy dimensions. The data from the first part of the study was used to develop a force indicator, designed to be a replica of the TAVI delivery device, and uses a colour light system to indicate to the surgeon if adequate force is being applied to accurately position the valve. The three equations derived after measuring the droop test of all leaflets are FL1 = -3.4831 x DroopL1 - 1.94, FL2 = -4.5872 x DroopL2 - 1.88, and FL3 = -4.7007 x DroopL3 – 1.70, fot the Right Coronary Cusps (RCC), Non-Coronary Cusps (NCC) and the Left Coronary Cusps (LCC) respectively. The forces required to position the valve accurately was calculated to be between 7.39N and 17.96N, for a minimum droop of 1.2mm and a maximum droop of 4.6mm. The C section of the C-arm is made of aluminium, the C arm can move and be locked into position when the adequate image is obtained using 2 different locking mechanisms. It is designed to hold a camera that can project images into a screen, replicating fluoroscopy images. The circulation loop was 3D printed, using parts made of clear silicone and clear rigid material, a valve was deployed inside using a delivery device de-aired with a solution mixed with food colouring to confirm visibility during the procedure without the use of X-ray. Images were taken during the deployment and compared to the X-ray images and the images obtains could be used as substitute of fluoroscopy images to train surgeons. The force indicator was designed with a light that shines blue when the force applied is less than 7.39N the light shines green when the force applied is between 7.39N and 17.96N and the light shines red when the force applied is greater than 17.39N. majority of the parts were 3D printed. The force indicator was built and tested to confirm that the light shined as designed. This will give a good tactile feedback indication to the surgeon to know when adequate force is applied. The three systems designed, used in conjunction, can be used to train surgeons on the TAVI without being exposed to any radiation, obtain adequate imaging, and apply the appropriate force to accurately position the valve.